If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + 3 = -4 + 18x Combine like terms: -1 + 3 = 2 2 = -4 + 18x Solving 2 = -4 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 2 + -18x = -4 + 18x + -18x Combine like terms: 18x + -18x = 0 2 + -18x = -4 + 0 2 + -18x = -4 Add '-2' to each side of the equation. 2 + -2 + -18x = -4 + -2 Combine like terms: 2 + -2 = 0 0 + -18x = -4 + -2 -18x = -4 + -2 Combine like terms: -4 + -2 = -6 -18x = -6 Divide each side by '-18'. x = 0.3333333333 Simplifying x = 0.3333333333
| 2x+9=-33-5x | | x*x/12+34=666 | | x.x/12+34=666 | | 3(2)+y=0 | | -8+2x=-6+8x | | 3/5x/2=234 | | 2(1)+y=0 | | 3/5x/2=6x | | 15/2= | | (7+u)(3u-2)=0 | | y^2-6y+36=0 | | X=-3x*-x | | (10/3)(37/7) | | -3(v+3)=-8v+11 | | -15=13+3f | | 3x+1y=17 | | -28=3y-7 | | 15-4d=31 | | 9*x+17-7=2+26 | | 2(0)-y=5 | | 5(6p-9)=26 | | 4x-34=180-4x-34 | | 4x-2+10=3*6 | | -2(3c+10)=8 | | 4y+5=5y+15 | | u/13=3/17 | | 3+42x=28x+15 | | 6xsquared-11x-10=0 | | 7x+5y+9z-2x+5z-6y= | | [(5x^2)/(8y^2)]*[(16y^6)/(x^3)] | | 37-4x=5-8x | | 3ab^2(10a^2b^3+8ab)= |